2010
DOI: 10.3109/10826081003682909
|View full text |Cite
|
Sign up to set email alerts
|

Waterpipe Use Predicts Progression to Regular Cigarette Smoking Among Danish Youth

Abstract: Waterpipe smoking among Danish, Swedish, and German youth is increasing dramatically, indicating the emergence of a new health threat. This study assessed the association between waterpipe smoking and progression to regular cigarette smoking among Danish continuation school students during 2004-2005. All participants (N = 762) had smoked cigarettes on a nonregular basis at baseline. Among boys, waterpipe smoking frequency was predictive of being a regular cigarette smoker at follow-up eight months later. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 19 publications
5
74
1
1
Order By: Relevance
“…However, despite these findings, it should be noted that a significant proportion of US adolescent hookah users in this sample also have never used cigarettes (33.7%) or e-cigarettes (36%). These findings elicit concerns that hookah may frequently be a product of first use, or act as a gateway to other tobacco use 34,35 . Clearly, more research is needed to further elucidate the connections between product of initiation, trying multiple products, and future smoking patterns.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite these findings, it should be noted that a significant proportion of US adolescent hookah users in this sample also have never used cigarettes (33.7%) or e-cigarettes (36%). These findings elicit concerns that hookah may frequently be a product of first use, or act as a gateway to other tobacco use 34,35 . Clearly, more research is needed to further elucidate the connections between product of initiation, trying multiple products, and future smoking patterns.…”
Section: Discussionmentioning
confidence: 99%
“…*p<0.05; **p<0.01; ***p<0.001. Danish adolescents has found that cigarette smokers who used waterpipe were more likely to report increased cigarette smoking intensity at followup than their counterparts who smoked cigarettes only 35 . Saunders and Geletko 36 found that adolescent cigarette smokers who used one form of ATP were more likely to use other types of ATPs.…”
Section: Resultsmentioning
confidence: 99%
“…There is a paucity of data on the persistence of hookah tobacco smoking among young adults, but one prospective study observed that half the sample continued to smoke hookah tobacco four years later (66). Other longitudinal data show that hookah tobacco smoking increases the likelihood of persistent cigarette smoking among individuals who have a prior history of cigarette smoking (67,68).…”
Section: Patterns Of Hookah Smokingmentioning
confidence: 99%